(untitled) (Journal of the College of Basic Education, 2022)
Over the course of a year, starting from October 2002 until the end of September 2003, 296 coarse fish Liza abu (Heckel) were collected from various markets in Baghdad to sell fish. Through the internal examination of the fish, the spiny-headed worm Neoechinorhynchus iraqensis was found in these fish, and a full description was given with the measurements used in diagnosing this worm.